2016
DOI: 10.1016/j.expthermflusci.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of density fluctuations using digital holographic interferometry in a standing wave thermoacoustic oscillator

Abstract: a b s t r a c tThis paper describes an optical set-up for measuring density fluctuations associated to acoustic oscillations in a thermoacoustic prime-mover. A time-resolved, full-field holographic interferometry technique is used, which enables to measure the optical phase difference between a reference beam and a probe beam passing through the acoustic resonator. The paper first presents the experimental set-up and the processing of holograms from which the instantaneous variations of the gas density along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…A model for temperature fluctuations developed by Gusev et al 20 predicts a nonlinear character of the temperature oscillations close to the stack. Berson et al 21 and Penelet et al 1 experimentally confirmed the appearance of harmonics. Even though no harmonic decomposition has been made in the present study, Figure 15 strongly supports the hypothesis of nonlinearities in the temperature signal clearly visible for point A.…”
Section: Temperaturementioning
confidence: 89%
See 2 more Smart Citations
“…A model for temperature fluctuations developed by Gusev et al 20 predicts a nonlinear character of the temperature oscillations close to the stack. Berson et al 21 and Penelet et al 1 experimentally confirmed the appearance of harmonics. Even though no harmonic decomposition has been made in the present study, Figure 15 strongly supports the hypothesis of nonlinearities in the temperature signal clearly visible for point A.…”
Section: Temperaturementioning
confidence: 89%
“…where χ is the temperature coefficient of resistivity and R 0 the resistance of the wire at the reference temperature T 0 . For an ideal cold wire devoid of thermal inertia and placed in a flow of instantaneous temperature T a (t), relation (1) gives…”
Section: A Correction Of the Thermal Inertia Of A Wirementioning
confidence: 99%
See 1 more Smart Citation
“…In practice, this suppression is achieved more or less empirically by means of jetpumps' 17 membranes 19 or tapered tubes. 92 However, Penelet et al 93 have shown that the amplification may actually be increased by the streaming through its influence on the shaping of the temperature field.…”
Section: Non-linear Mechanisms In Thermoacousticsmentioning
confidence: 99%
“…For example, the plankton and other marine organisms as well as bacteria and fruit flies have been explored using the DH method (Sun et al, 2007;Xu et al, 2001). The density fluctuations of a standing wave in a thermoacoustic oscillation (Penelet et al, 2015) and the phase compensation of spherical beam (Sánchez-Ortiga et al, 2011) have been analyzed by the hologram patterns as well. The fingerprint patterns of human can also be observed and separated by investigating their profile intensity fringes (Plaipichit and Buranasiri, 2014).…”
Section: Introductionmentioning
confidence: 99%